Using Mobility and Blackboards to Support a Multiparadigm Model Oriented to Distributed Processing - Barbosa, Jorge Luis Victória; Yamin, Adenauer Corrêa; Vargas, Patrícia Kayser; Ferrari, Débora Nice; Schaeffer, Alberto Egon; Geyer, Cláudio Fernando Resin (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
Holoparadigm (Holo) is a multiparadigm model oriented to development of parallel and distributed programs. In this paper we propose the Distributed Holo (DHolo), a model to support the distributed execution of programs developed in Holo. DHolo is based on object mobility and blackboards. This distributed model can be fully implemented on Java platform. Specifically, mobility is implemented using Voyager and blackboard using Jada tuple space.